Trainees' Cultural Humility and Implicit Associations about Clients and Religious, Areligious, and Spiritual Identities: A Mixed-Method Investigation. Issue 3 (September 2019) - Winkeljohn Black, Stephanie; Gold, Amanda P.
Therapists' cultural humility is associated with stronger client–therapist working relationships, though therapist trainees' cultural humility toward clients of diverse religious, areligious, or spiritual (RAS) backgrounds is unknown. This is compounded by a lack of systemic training in RAS diversity within clinical and counseling psychology programs. The current, mixed-method pilot study ( N = 10) explored psychotherapy trainees' self-reported and implicit attitudes (via Implicit Association Tasks) toward RAS diversity in clients, and then used a focus group to explore whether trainee responses to feedback about their implicit attitudes imbued themes of cultural humility that supervisors and educators could use as discussion points to heighten cultural humility and responsiveness in trainees. There was no association between trainees' self-reported and implicit RAS attitudes; participant responses revealed cultural humility themes, including receptivity and openness to feedback (i.e., their levels of implicit attitudes toward RAS groups).